Aesthetics of movement with sight disabled children - pilot study - Mirosław Górny (Palacký University Olomouc, 2010)
The aim of the study was to establish the aesthetics of movement in people with vision defects. This knowledge will provide tools to improve the methodology of study in the area of assessment of movement aesthetics in people with disabilities. In order to establish its level a test was used which measured its selected elements such as precision, rhythm, harmony, fluidity and speed. The aesthetics of movement was assessed using exercise tests which were to represent the components of aesthetics of movement. Individual tests were carried out on blind and partially sighted children aged 6 to 15 years and on a group of healthy children of the same age. Using the test tasks a general indicator of movement aesthetics in blind children was obtained. The participants of the study were 145 children from four School and Education Centres for Blind Children in Poland and the control group consisted of 310 children from a primary school in Poznań. The studies confirmed a lower level of movement aesthetics in children with vision defects, but the diﬀerences in groups between the partially sighted children and children with correct vision were definitely smaller. A higher level of aesthetics of movement characterised children from older groups irrespective of their sex. The best developed property in blind and partially sighted children was precision.